Roles of nutrition in muscle health of community‐dwelling older adults: evidence‐based expert consensus from Asian Working Group for Sarcopenia. Issue 3 (20th March 2022) - Chen, Liang‐Kung; Arai, Hidenori; Assantachai, Prasert; Akishita, Masahiro; Chew, Samuel T.H.; Dumlao, Lourdes Carolina; Duque, Gustavo; Woo, Jean
Abstract: General muscle health declines with age, and in particular, sarcopenia—defined as progressive loss of muscle mass and strength/physical performance—is a growing issue in Asia with a rising population of community‐dwelling older adults. Several guidelines have addressed early identification of sarcopenia and management, and although nutrition is central to treatment of sarcopenia, there are currently few guidelines that have examined this specifically in the Asian population. Therefore, the Asian Working Group for Sarcopenia established a special interest group (SIG) comprising seven experts across Asia and one from Australia, to develop an evidence‐based expert consensus. A systematic literature search was conducted using MEDLINE on the topic of muscle health, from 2016 (inclusive) to July 2021, in Asia or with relevance to healthy, Asian community‐dwelling older adults (≥60 years old). Several key topics were identified: (1) nutritional status: malnutrition and screening; (2) diet and dietary factors; (3) nutritional supplementation; (4) lifestyle interventions plus nutrition; and (5) outcomes and assessment. Clinical questions were developed around these topics, leading to 14 consensus statements. Consensus was achieved using the modified Delphi method with two rounds of voting. Moreover, the consensus addressed the impacts of COVID‐19 on nutrition, muscle health, and sarcopenia in Asia. These statements encompass clinical expertise and knowledge across Asia and are aligned with findings in the current literature, to provide a practical framework for addressing muscle health in the community, with the overall aim to encourage and facilitate broader access to equitable care for this target population.